Lisinopril increases lung ACE2 levels and SARS-CoV-2 viral load and decreases inflammation but not disease severity in experimental COVID-19 - Silva-Santos, Yasmin; Pagni, Roberta Liberato; Gamon, Thais Helena Martins; de Azevedo, Marcela Santiago Pacheco; Bielavsky, Mônica; Darido, Maria Laura Goussain; de Oliveira, Danielle Bruna Leal; de Souza, Edmarcia Elisa; Wrenger, Carsten; Durigon, Edson Luiz; Luvizotto, Maria Cecília Rui; Ackerman, Hans Christian; et al. (Frontiers in Pharmacology, 2024)
COVID-19 causes more severe and frequently fatal disease in patients with pre-existing comorbidities such as hypertension and heart disease. SARS-CoV-2 virus enters host cells through the angiotensinconverting enzyme 2 (ACE2), which is fundamental in maintaining arterial pressure through the reninangiotensin system (RAS). Hypertensive patients commonly use medications such as angiotensinconverting enzyme inhibitors (ACEi), which can modulate the expression of ACE2 and, therefore, potentially impact the susceptibility and severity of SARS-CoV-2 infection. Here we assessed whether treatment of ACE2-humanized (K18-hACE2) mice with the ACEi Lisinopril affects lung ACE2 levels and the outcome of experimental COVID-19. K18-hACE2 mice were treated for 21 days with Lisinopril 10 mg/kg and were then infected with 10 5 PFU of SARS-CoV-2 (Wuhan strain). Body weight, clinical score, respiratory function, survival, lung ACE2 levels, viral load, lung histology, and cytokine (IL-6, IL-33, and TNF-α) levels were assessed. Mice treated with Lisinopril for 21 days showed increased levels of ACE2 in the lungs. Infection with SARS-CoV-2 led to massive decrease in lung ACE2 levels at 3 days post-infection (dpi) in treated and untreated animals, but Lisinopril-treated mice showed a fast recovery (5dpi) of ACE2 levels. Higher ACE2 levels in Lisinopril-treated mice led to remarkably higher lung viral loads at 3 and 6/7dpi. Lisinopril-treated mice showed decreased levels of the pro-inflammatory cytokines IL-6 and TNF-α in the serum and lungs at 6/7dpi. Marginal improvements in body weight, clinical score and survival were observed in Lisinopril-treated mice. No differences between treated and untreated infected mice were observed in respiratory function and lung histology. Lisinopril treatment showed both deleterious (higher viral loads) and beneficial (antiinflammatory and probably anti-constrictory and anti-coagulant) effects in experimental COVID-19. These effects seem to compensate each other, resulting in marginal beneficial effects in terms of outcome for Lisinopril-treated animals.